Weakened Increase in Global Near‐Surface Water Vapor Pressure During the Last 20 Years - Wenfang Xu; Xiaosheng Xia; Shilong Piao; Donghai Wu; Weibiao Li; Song Yang; Wenping Yuan (Geophysical Research Letters)
Abstract It is well known that global warming increases the atmospheric water vapor content, which results in substantial changes in the hydrological cycle. Using five observational data sets, the results show that an increasing trend of near‐surface water vapor pressure (AVP) over land and ocean was significant from 1975 to 1998, while such an increasing trend in AVP subsequently weakened from 1999 to 2019. This phenomenon is associated with decreased oceanic evaporation and land surface evapotranspiration in response to recent climate variations. One consequence of such a phenomenon is a large increase in near‐surface vapor pressure deficit (VPD), which in turn increases atmospheric demand for water vapor and thus aridity and drought over land. This result emphasizes the importance of water vapor change under global warming.